The answer will be 8.39 because the third number (8) is above 5 so you have to round up. Good luck!
Answer:
(0, - 3 ) and (- 1, - 5 )
Step-by-step explanation:
Given the 2 equations
y = 4x² + 6x - 3 → (1)
y = 2x - 3 → (2)
Substitute y = 4x² + 6x - 3 into (2)
4x² + 6x - 3 = 2x - 3 ( subtract 2x - 3 from both sides )
4x² + 4x = 0 ← factor out 4x from each term
4x(x + 1) = 0
Equate each factor to zero and solve for x
4x = 0 ⇒ x = 0
x + 1 = 0 ⇒ x = - 1
Substitute these values into (2) for corresponding values of y
x = 0 : y = 2(0) - 3 = 0 - 3 = - 3 ⇒ (0, - 3 )
x = - 1 : y = 2(- 1) - 3 = - 2 - 3 = - 5 ⇒ (- 1, - 5 )
Answer:
Step-by-step explanation:
5
Answer:
19/2
Step-by-step explanation :
U divide the numerator and the denominator by the same number which is 3
57 divided by 3 = 19
6 divid by 3 = 2
So the answer is 19/2